Drought decreases incorporation of recent plant photosynthate into soil food webs regardless of their trophic complexity. (10th August 2019) - Chomel, Mathilde; Lavallee, Jocelyn M.; Alvarez‐Segura, Nil; de Castro, Francisco; Rhymes, Jennifer M.; Caruso, Tancredi; de Vries, Franciska T.; Baggs, Elizabeth M.; Emmerson, Mark C.; Bardgett, Richard D.; Johnson, David
Abstract: Theory suggests that more complex food webs promote stability and can buffer the effects of perturbations, such as drought, on soil organisms and ecosystem functions. Here, we tested experimentally how soil food web trophic complexity modulates the response to drought of soil functions related to carbon cycling and the capture and transfer below‐ground of recent photosynthate by plants. We constructed experimental systems comprising soil communities with one, two or three trophic levels (microorganisms, detritivores and predators) and subjected them to drought. We investigated how food web trophic complexity in interaction with drought influenced litter decomposition, soil CO2 efflux, mycorrhizal colonization, fungal production, microbial communities and soil fauna biomass. Plants were pulse‐labelled after the drought with 13 C‐CO2 to quantify the capture of recent photosynthate and its transfer below‐ground. Overall, our results show that drought and soil food web trophic complexity do not interact to affect soil functions and microbial community composition, but act independently, with an overall stronger effect of drought. After drought, the net uptake of 13 C by plants was reduced and its retention in plant biomass was greater, leading to a strong decrease in carbon transfer below‐ground. Although food web trophic complexity influenced the biomass of Collembola and fungal hyphal length, 13 C enrichment and the net transfer of carbon from plant shoots to microbes and soil CO2 efflux were not affected significantly by varying the number of trophic groups. Our results indicate that drought has a strong effect on above‐ground–below‐ground linkages by reducing the flow of recent photosynthate. Our results emphasize the sensitivity of the critical pathway of recent photosynthate transfer from plants to soil organisms to a drought perturbation, and show that these effects may not be mitigated by the trophic complexity of soil communities, at least at the level manipulated in this experiment. Abstract : How soil food web complexity modulates the response to drought of soil functions related to C cycling and the capture and transfer below‐ground of recent photosynthate C by plants? We provide an exciting 13 C pulse‐labelling experiment to answer that question. We used experimental mesocosms with one, two or three trophic groups and subjected them to a drought and then to a 13 C pulse‐labelling. Overall, our results show that drought and soil food web complexity do not interact to affect the soil functions related to C cycling and microbial community composition, but independently affect carbon cycling, with an overall stronger effect of drought.